A comparable study on the deterioration of limestone powder blended cement under sodium sulfate and magnesium sulfate attack at a low temperature. (20th May 2020) - Wu, Meng; Zhang, Yunsheng; Ji, Yongsheng; She, Wei; Yang, Lin; Liu, Guojian
Highlights: The performance of PLC under sodium sulfate and magnesium sulfate attack at 5 °C were investigated. The differences of sodium sulfate and magnesium solution during the TSA failure were studied and discussed. The amount of corrosion products of PLC under sulfate attack at 5 °C were quantified and compared. Abstract: The deterioration mechanisms and corrosion products of Portland cement blended with limestone powder (PLC) exposed to external sulfate solutions at 5 ± 1 °C were investigated in the present study. The damage degree of paste specimens was evaluated by the evolution of appearance, strength and volume. Furthermore, to identify and quantitatively analyse the compositions of corrosion products during sulfate attack, Fourier transform infrared spectroscopy, quantitative X-ray powder diffraction and electron microprobe analysis were applied in this study. The results showed that the PLC were seriously damaged after immersion for 360 days due to the expansion of volume and the loss of strength. Moreover, the type of sulfate solution had great influence on the compositions of corrosion products from PLC immersed in sulfate solutions at low temperatures. The corrosion products of PLC immersed in sodium sulfate solution were mainly composed of thaumasite and ettringite. However, in scenario of magnesium sulfate solution, the corrosion products were basically gypsum coupled with thaumasite. The analysis results indicated that the low pH value of pore solution and decalcification effect due to magnesium sulfate attack was probably beneficial for thaumasite formation by transformation of ettringite (woodfordite route), while the sodium sulfate seemed to favour the formation of thaumasite via direct route.